Understanding practitioners' and young people's views of a risk calculator for future psychopathology and poor functioning in young people victimised during childhood. (2nd November 2021) - Latham, Rachel M.; Temple, Rachel K.; Romeo, Crystal; Danese, Andrea; Fisher, Helen L.
Abstract: Background: Although children who are exposed to victimisation (including abuse, neglect, domestic violence and bullying) have an increased risk of later psychopathology and functional impairment, not all go on to develop these outcomes. Risk calculators that generate individualised probabilities of a victimised child developing future psychopathology and poor functioning have the potential to help practitioners identify the most vulnerable children and efficiently target preventive interventions. Aim: This study explored the views of young people and practitioners regarding the acceptability and feasibility of potentially using a risk calculator to predict victimised children's individual risk of poor outcomes. Methods: Young people ( n  = 6) with lived experience of childhood victimisation took part in two focus groups. Health and social care practitioners ( n  = 13) were interviewed individually. Focus groups and interviews were audio-recorded, transcribed and thematically analysed. Results: Ten themes were identified, organised according to the three main topics of discussion: (i) identifying risk (risk factors, current practice, accuracy, implementation, response); (ii) protective factors and prevention (individual, environment, preventative intervention); and (iii) communication of research (stakeholders, methods). Conclusion: Risk calculators have the potential to enhance health and social care practice in the United Kingdom, but we highlight key factors that require consideration for successful implementation.